Redbull lumba kapcai event: brand awareness / Aliff Asyraf Mohamad Shukeri - Mohamad Shukeri, Aliff Asyraf (Faculty of Art and Design, 2020)
Redbull Lumba Kapcai is the first Malaysian youth motorcycle racing events with the category under bone at International Sepang Circuit Malaysia.